2019
DOI: 10.1590/0034-737x201966040004
|View full text |Cite
|
Sign up to set email alerts
|

Morphological characterization of Coelogyne spp for germplasm conservation of orchids

Abstract: Orchid is one of the ornamental plant that has a high aesthetic value. Efforts to increase the quality of orchids can be done by genetic improvement through crossing. The first step to success in orchid crossing requires information on morphological characters of the prospective parents. This study aims to determine the similarity of six species of natural Coelogyne spp based on qualitative morphological characters. Morphological characterization of 6 orchids was carried out based on 30 characters including st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 15 publications
1
10
0
3
Order By: Relevance
“…(De et al 2015b;Darmawati et al 2018;Indraloka et al 2019), Coelogyne spp. (Hartati et al 2019a); Phaius spp. (Devadas et al, 2019;Hartati et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…(De et al 2015b;Darmawati et al 2018;Indraloka et al 2019), Coelogyne spp. (Hartati et al 2019a); Phaius spp. (Devadas et al, 2019;Hartati et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, cytological studies have shown that the karyotype of C. pandurata is 2n=56, C. rumphii is 2n=72 and their hybrid is 2n=54 (Hartati et al 2017). A second study showed that based on the morphological identification of these two species, they have a morphological similarity of 87% (Hartati et al 2019a). Furthermore, the crosses of C. pandurata and C. rumphii are 100% successful using selfing, crossing, and reciprocal methods (Hartati et al 2019b).…”
Section: Introductionmentioning
confidence: 99%
“…Our results are similar to those of Mat-Yasin et al [14], who investigated the propagation medium of Spathoglottis plicata. Hartati et al [15] found that the addition of NAA and coconut water to medium for in vitro black orchid propagation has increasing number of roots. However, at physiological concentrations, cytokinins activate the shoot apical meristem and shoot growth but suppress the root apical meristem and root growth [16] Cytokinins promote cell division, stimulate the release of lateral buds from apical dominance, delay leaf senescence, and enhance chloroplast development.…”
Section: Resultsmentioning
confidence: 99%